Strategi Pedagang Tradisional di Pasar Panorama Kota Bengkulu dalam Menghadapi Tantangan E-Commerce: Strategi Pedagang Tradisional di Pasar Panorama Kota Bengkulu dalam Menghadapi Tantangan E-Commerce - Ayu Wijayanti; Putri Nikmah Safas; Linda Safitra (Jurnal Sosiologi Nusantara, 2024)
The growth of e-commerce has created significant challenges for traditional traders at Panorama Market, Bengkulu City. Many traders face difficulties competing with online platforms that offer lower prices and easier access. This study aims to analyze the adaptation strategies adopted by traditional traders to address these changes and sustain their businesses. A qualitative approach is used in this research, with data collection techniques that include observation, interviews, and documentation. The findings show that although some traders struggle with technology, others have successfully adapted to e-commerce disruption by using social media and e-commerce platforms such as Facebook, TikTok, Shopee, and Tokopedia to expand their market reach. Additionally, word-of-mouth promotion within local communities, like trader and market associations, has proven effective for promoting products and maintaining customer loyalty. Based on Manuel Castells' information economy theory, combining social media and e-commerce platforms with offline interactions strengthens traders' social ties and enhances their competitiveness. Thus, traditional traders at Panorama Market have the potential to adapt, leverage technology, and compete in the digital era.